Expatriates Cultural Adjustment: Empirical Analysis On Individual Cultural Orientation - Tsegaye, Wondwossen Kassa; Su, Qin (Journal of Applied Business Research, 2017)
Previous researches have shown that expatriates` failure rate has steadily increased in recent years. The failure of expatriates mainly related with the cross-cultural challenges. The purpose of this study was to identify factors which have a paramount implication on expatriates’ cultural adjustment. Hierarchical regression and MANCOVA were applied in data analysis. Hofstede’s (1980) cultural dimension scores were used to measure culture at national level. The individual cultural orientation was measured using a scale that used Hofstede (1980) dimensions as a framework. Moreover, a recently developed model was adopted to analyze the expatriate adjustment. Cultural adjustment found to be affected more by individual cultural orientation than national culture differences among expatriates` home and host countries. The alignment of the expatriate cultural orientation with the national culture found to be critical for effective expatriate cultural adjustment. The result indicated that gender difference does not have a significant role in expatriate cultural adjustment. This research would have a conceptual contribution in comprehensively assessing individual cultural orientation with cognitive expatriate adjustment. The study indicated factors that MNCs managers would use for effective selection and assignment of expatriates.
Keywords: Expatriates; Cultural Adjustment; Individual Cultural Orientation; Culture Distance